The effects of Ivomec on experimental infection of Awasi lambs by H. contortus - حسن عيسى, وفاء (The Iraqi Journal of Veterinary Medicine, 1996)
The effect of Ivomec was studied against stomach large worm H. contortus in experimental Awasi lambs through infection of 500 infective larvac per Kg body weight. Result revealed that Ivomec has high efficacy reaching 100%. Two weeks post treatment, improvment of blood parameter was recorded 3 weeks post treatment indicating its effectivness, there was also decrease in the number of eggs per gram which vanished 2 weeks post treatment. This indicated that Ivomec with a fixed dose has high efficacy against H. contortus the most spread helminth in Iraq